“I’ve had constant fears that I’ll get cancer”: the construction and experience of medical intervention on intersex bodies to reduce cancer risk - Jane M. Ussher; Morgan Carpenter; Rosalie Power; Samantha Ryan; Kimberley Allison; Bonnie Hart; Alexandra Hawkey; Janette Perz (International Journal of Qualitative Studies on Health & Well-Being)
Purpose This paper examines the subjective experience of medical interventions on intersex bodies to reduce cancer risk. Methods Twenty-five individuals with intersex variations took part in semi-structured interviews, analysed through thematic discourse analysis. Results Intersex bodies were positioned as inherently sick and in need of modification, with cancer risk legitimating surgical and hormonal intervention. This resulted in embodied shame, with negative impacts on fertility and sexual wellbeing. However, many participants resisted discourses of bio-pathologisation and embraced intersex status. Some medical interventions, such as HRT, were perceived to have increased the risk of cancer. Absence of informed consent, and lack of information about intersex status and the consequences of medical intervention, was positioned as a human rights violation. This was compounded by ongoing medical mismanagement, including health care professional lack of understanding of intersex variations, and the objectification or stigmatization of intersex people within healthcare. The consequence was non-disclosure of intersex status in health contexts and lack of trust in health care professionals. Conclusions The legitimacy of poorly-evidenced cancer risk discourses to justify medical intervention on intersex bodies needs to be challenged. Healthcare practitioners need to be provided with education and training about cultural safety practices for working with intersex people.